Canine urothelial carcinoma: expression of Periostin in spontaneous canine urothelial carcinoma and its correlation with histological features - Brambilla, Eleonora; Ciaputa, Rafał; Crepaldi, Paola; Dzimira, Stanislaw; Nowak, Marcin; Dziegiel, Piotr; Piotrowska, Aleksandra; Mollica Govoni, Veronica; Fonseca-Alves, Carlos Eduardo; Laufer-Amorim, Renée; Stefanello, Damiano; Romussi, Stefano; et al. (Frontiers in Veterinary Science, 2023)
The tumor microenvironment is considered one of the main players in cancer development and progression and may influence the cancer cells' behavior. Periostin (POSTN) is an extracellular matrix protein, and its main functions are induction of fibrillogenesis, fibroblastic cell proliferation and migration, enhancing regeneration in normal tissue and promoting metastasis in case of neoplasia. POSTN was already studied in humans in several normal tissues, inflammatory processes and neoplasms revealing an important role for tumor progression in various types of cancer, such as colon, lung, head and neck, breast, ovarian, and prostate. In these latter, high levels of POSTN are usually associated with a more aggressive tumor behavior, tumor advanced stages and poor prognosis while, in human bladder urothelial carcinoma (BUC), unlike in most tumors, POSTN expression seems to be down-regulated. The expression of this marker has been poorly investigated in veterinary medicine thus the aim of this study was to immunohistochemically investigate the presence and the intensity of POSTN expression in canine BUCs and to determine a possible relationship between POSTN This is a provisional file, not the final typeset article expression and histopathological features such as mitotic count, muscular and vascular invasion. For the present retrospective study, archived samples from 45 canine BUCs and 6 non-neoplastic canine bladders were considered for histological evaluation and immunohistochemical examination for the expression of POSTN. POSTN expression was semi-quantitatively assessed considering both the percentage of the neoplastic stroma positive for POSTN and the intensity of the immunohistochemical labelling. Histologically, 38/45 tumors were papillary and 7/45 non-papillary. All tumors were infiltrating, being that 21 were muscle-invasive and a significant correlation between this feature and the presence of vascular invasion emerged (P = 0.0001). In normal bladder tissue, as reported in humans, a thick strongly positive belt of POSTN was visible and, in canine BUCs, stating that expression is comparable with human benign as well as malignant bladder tissue, a general decrease in POSTN expression was observed except for a strongly labelled ring of POSTN observed around some neoplastic nodules infiltrating the muscle layer. Moreover, POSTN expression and mitotic count were significatively inversely correlated (P-value=0.0015).